The prognostic value of pretreatment inflammatory and nutrition-related indices in patients with cardia cancer - Guo, Wenjuan; Zhao, Jinwei; Li, Ning; Wang, Jing (Frontiers in Nutrition, 2025)
ObjectiveTo evaluate the prognostic significance of inflammatory and nutrition-related indexes in patients with cardia cancer prior to treatment.MethodsA total of 229 patients with cardia cancer, diagnosed pathologically and admitted to Shanxi Cancer Hospital between January 2017 and December 2018, were included. Statistical analysis was conducted using SPSS 26.0, and the optimal cut-off values for body mass index (BMI), peripheral blood platelet-to-lymphocyte ratio (PLR), hemoglobin-to-erythrocyte distribution width ratio (HRR), prognostic nutritional index (PNI), and integrating hemoglobin, albumin, lymphocyte, and platelets (HALP) score were determined with X-tile 3.6.1 software. Survival analysis was performed using the Kaplan–Meier method, with variability assessed by the Log-rank test. Univariate and multivariate Cox proportional hazards regression analyses were used to evaluate the prognostic value of the variables. A prognostic risk stratification model was developed, incorporating age, tumor node metastasis classification (TNM), treatment options, HRR, and PNI, to classify patients into low-risk, intermediate-risk, high-risk, and very high-risk groups. The predictive value of the model was assessed using receiver operating characteristic (ROC) curves.ResultsThe optimal critical values of BMI, PLR, HRR, PNI, and HALP score were 20.43 kg/m2, 140.59, 2.85, 49.98, and 28.23, respectively. Cox univariate analysis showed that age, TNM stage, treatment regimen, BMI, PLR, HRR, PNI, and HALP score were correlated with the prognosis of patients with cardia cancer (p < 0.05). The results of Cox multifactorial analysis showed that age, TNM stage, treatment regimen, HRR, and PNI were independent factors affecting the prognosis of patients with cardia cancer (p < 0.05). Age ≥ 60 years, TNM stage III/IV, treatment regimen without surgical involvement, HRR < 2.85, and PNI < 49.98 were considered as risk factors. These five variables were assigned points based on their HRs. The patients were categorized as low-risk (0–6 points), intermediate-risk (7–8 points), high-risk (9 points), and very-high-risk (10–11 points) groups. The median survival times were undefined, 18.05 months, 15.63 months, and 9.10 months, respectively, with statistically significant differences among the four groups (p < 0.05). ROC curve analysis, the area under the curve (AUC) of the prognostic risk stratification model was 0.80, which was higher than those for age (0.56), TNM stage (0.63), treatment regimen (0.73), HRR (0.57), and PNI (0.63).ConclusionPre-treatment inflammatory and nutrition-related indexes, HRR and PNI, were closely associated with the prognosis of patients with cardia cancer. Combining age, TNM stage, treatment regimen, HRR, and PNI for prognostic risk stratification could significantly enhance the accuracy of prognostic predictions.